Magnetic properties of mechanically-alloyed Sm-Co nanophase hard magnets - VENKATESAN, MUNUSWAMY; COEY, JOHN MICHAEL DAVID (IEEE, 2001)
Highly coercive Sm14Co86 powders were prepared by mechanical alloying with a view to enhance the high temperature magnetic properties by optimizing the annealing conditions. The powders were annealed in quartz tubes with a continuous vacuum of ~10-6 mbar at different temperatures. X-Ray diffraction studies confirmed the formation of a disordered 2:17 phase. DTA measurement on the as-milled amorphous powders revealed a single crystallization event at around 500?C. Magnetic measurements showed room temperature coercivities of at least 1 T and Curie temperatures around 820?C. The behavior of the initial magnetization curve lies in between those observed for low Hc 2:17 precipitation hardened magnets and SmCo5 or Nd2Fe14B magnets. The magnitude of coercivity is found to be sensitive to annealing temperature. The detailed comparison of magnetic properties with annealing conditions will be presented
PUBLISHED
Keywords: Physics